DETERMINATION OF MEDIAN LETHAL CONCENTRATION AND BEHAVIOURAL EFFECTS OF TRICLOSAN IN Heteropneustes fossilis - VANDANA, B.; KAIPPALLIL, JOSE D. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
Triclosan is a broad spectrum antimicrobial agent found in medical, household and personal care products. Due to its widespread use and high persistence potential, triclosan, which is a chlorinated phenolic compound, ensures its presence in soil, surface water, drinking water etc. In this study acute toxicity tests were carried out, to evaluate the LC50 value of triclosan (5-chloro–2-(2,4dichlorophenoxy) phenol), for the period of 24, 48, 72 and 96 hr and to identify the behavioural alterations in the fish Heteropneustes fossilis. Using Finney’s probit analysis, the LC50 values were found and for 24, 48, 72 and 96 hours the LC50 values obtained were 9.54, 8.2, 7.59 and 7.14 mg/L respectively. Behavioural alterations like erratic movement, increased surfacing activity, haemorrhagic eyes, reddened fins, decreased operculum movements, body tremors, increased mucous deposition all over the body and lose of equilibrium were also observed in the fishes. These results of toxicity test revealed the toxic effect of triclosan in Heteropneustes fossilis.